Fuzzy logic motor speed controller for soccer playing robots - Vicerra, Ryan Rhay P. (Animo Repository, 2009)
This study is focused in the design, development and benchmarking of a fuzzy logic motor speed controller for soccer playing robots. It is coded in Clanguage for an Atmel ATmega128 Microcontroller. The inputs for the fuzzy logic are the left velocity and right velocity that is sent by the host computer. While they are referred to as velocities, these values are simple a range of numbers representing stop, the slowest up to the fastest velocity for both forward and reverse. The fuzzy logic motor speed controller converts these values to the actual velocity to be performed by the motors. Also, the fuzzy logic motor speed controller made it possible to compensate the errors produced by motor differences. A series of drills and experiments were done to benchmark the Fuzzy Logic Motor Speed Controller versus the original non-fuzzy controller of the Neuronemech soccer robots. As shown in the test results and actual performance of the robots, the fuzzy logic motor speed controller is found to be effective in characterizing the speed assignment and resolution of a specific motor and performed better than the original non-fuzzy logic controller.